2019
DOI: 10.3390/en12193624
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flow Fields Over a 3D Hill Covered by Vegetation Canopy Through Large Eddy Simulations

Abstract: The flow fields over a simplified 3D hill covered by vegetation have been examined by many researchers. However, there is scarce research giving the three-dimensional characteristics of the flow fields over a rough 3D hill. In this study, large eddy simulations were performed to examine the coherent turbulence structures of the flow fields over a vegetation-covered 3D hill. The numerical simulations were validated by the comparison with the wind-tunnel experiments. Besides, the flow fields were systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Other work extended these arguments by including longitudinal advection and mean vertical velocity-pressure interactions, but the generic features of the recirculation zone were not altered (Poggi et al, 2008). Most of these features have been supported by LES studies of idealized topography such as isolated ridges (Dupont et al, 2008) and hills (Liu et al, 2019;Patton & Katul, 2009). The few studies that include real topography have focused on steeper slopes, for which separation would occur even in the absence of canopy cover (e.g., Grant et al, 2015Grant et al, , 2016Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Other work extended these arguments by including longitudinal advection and mean vertical velocity-pressure interactions, but the generic features of the recirculation zone were not altered (Poggi et al, 2008). Most of these features have been supported by LES studies of idealized topography such as isolated ridges (Dupont et al, 2008) and hills (Liu et al, 2019;Patton & Katul, 2009). The few studies that include real topography have focused on steeper slopes, for which separation would occur even in the absence of canopy cover (e.g., Grant et al, 2015Grant et al, , 2016Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Some of these studies have been for heterogeneous surfaces, such as windbreaks, forest edges, forest clearings, patches, leaf area index (LAI) inhomogeneity, and vineyards (Patton et al 1998;Albertson et al 2001;Yang et al 2006aYang et al , 2006bYang et al , 2006cBrunet 2008a, 2009;Cassiani et al 2008;Bohrer et al 2009;Dupont et al 2011Huang et al 2011;Schlegel et al 2012Schlegel et al , 2015Chahine et al 2014;Lopes et al 2015;Boudreault et al 2017;Nakao and Hattori 2019;Ma et al 2020). A comprehensive survey of LES studies of airflow in and above horizontally heterogeneous plant canopies and flows associated with plant canopies on hilly terrain and urban structures (Dupont et al 2008;Patton and Katul 2009;Ross 2011;Giometto et al 2016;Liu et al 2019;Nazarian et al 2020;Blunn et al 2022) is beyond the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group examined the modeling of flow fields over typical topographies extensively [27][28][29][30][31][32] ; however, we did not study the interactions between wind turbine wake and flow fields over various topographies. The literature survey indicated that even though the number of studies on the interaction between wind turbines and terrain has increased in recent years, there is yet no study considering the different features of the interaction between wind turbines and topographies with different shapes such as 3D and 2D hills.…”
mentioning
confidence: 99%